Significance of Tafsir Isyari Values in the Modern Era - Ahmad Syauky; Syabuddin, Syabuddin (Al-Shamela : Journal of Quranic and Hadith Studies, 2025)
Tafsir isyari is one of the styles of interpretation that is often used as an analysis of the verses of the Qur'an. In its interpretation, Tafsir isyari uses more conscience, because every verse in the Qur'an has a hidden meaning. This article aims to find out the application of the values of Tafsir isyari content in the modern era, so that Muslims can understand and apply the content implied in the Qur'an. By using qualitative methods and descriptive analysis through literature, this article can conclude that tafsir isyari interprets the verses of the Qur'an based on divine signs inspired by God to his servants. Although it has a more hidden inner dimension, it has a great influence in the modern era. In this context, Tafsir isyari provides spiritual depth that is relevant to the challenges of the times, while opening up space to answer social and moral problems in contemporary society. However, it also requires a careful and balanced approach so as not to get out of the original context of the Qur'an, so that the understanding given can still be accounted for both theologically and socially. This article contributes to enrich the study of the style of interpretation of the Qur'an that the significance of Tafsir isyari can be used as a guide for Muslims in spiritual and social life.